Revision of Recent and fossil Mixtacandona Klie 1938 (Ostracoda, Candonidae) from Italy, with description of a new species - Mazzini, Ilaria; Marrone, Federico; Arculeo, Marco; Rossetti, Giampaolo (Zootaxa, 2017)
Although studies on ostracods dwelling in inland subterranean habitats of Italy have increased in the last decades, highlighting a considerable taxonomic diversity, available information is still far from sufficient to understand phylogenetic and biogeographic relationships. Mixtacandona Klie 1938 is one of the most common and diverse genera of ostracods in subterranean waters. Of the 20 living recognized species in the genus, all stygobiontic and restricted to the Palearctic Region, four are known for the Italian peninsula and Sardinia, one of which exclusively as fossil. Several other Recent and fossil taxa attributable to Mixtacandona, but identified at supraspecific level, have been reported from various Italian regions. Here we report Mixtacandona idrisi n. sp., collected in a cave near Palermo, the first cavernicolous ostracod from the island of Sicily; in addition, the description of material recently collected in northern Italy, consisting of M. laisi and of a putative new species that has been tentatively allocated to the same genus, is given. Mixtacandona (Trapezicandona) italica Karanovic & Pesce, 2000 is tentatively treated as a junior synonym of M. talianae Gliozzi & Mazzini, 1998. The validity of species-groups within Mixtacandona is discussed. Relying on the results of this study, the authors argue for the need of a comprehensive revision of the genus.